THE BINARY OPPOSITION OF EMPATHY AND VIOLENCE IN MARK HERMAN’S THE BOY IN THE STRIPPED PAJAMAS THE MOVIE (English Department, Faculty of Languages and Arts, Universitas Negeri Semarang, 2013)
This study is attempted to analyze binary oppositions of Germans during WWII as reflected in the Boy in the Stripped Pajamas the Movie. The objectives are: 1) identifying the binary opposition of empathy and violence of German in the Boy in the Stripped Pajamas and 2) to know the things connected the empathic and violent Germans in the Boy in the Stripped Pajamas with Germany's historical background. I use qualitative descriptive research and structuralism approach in this research. Source of the data is the movie script and scenes of in the movie. The data collected in this research are consisting of words, phrases, sentences and implicit meaning found in scenes laid in the movie. In conducting this research, I used observation sheets as the instrument. The data are collected by reading the movie script, identifying supportive text, inventorying the data into table, and classifying the data. From the analysis I concluded that (1) the characters is divided into two opposite groups; empathic characters and violent characters (2) the fictional characters in the Boy in the Stripped Pajamas connected with its historical background through three matters; jealousy, misinterpreted belief and enthusiasm of aggressiveness.